Snakebite in domestic animals: First global scoping review - Bolon, Isabelle; Finat, Matias; Herrera, Maria; Nickerson, Andrea; Grace, Delia; Schütte, Stephanie; Martins, Sara B.; Ruíz de Castañeda, Rafael (Elsevier, 2019)
Snakebite is a Neglected Tropical Disease estimated to cause more than 100,000 human deaths and disable more than 400,000 victims each year. It primarily affects poor agricultural workers, farmers, and cattle herders living in rural areas of developing countries. It is thus an occupational disease. However, the impact of snakebite on these rural communities could be even higher if a One Health approach is taken to consider the direct impact on domestic animals and indirect impact on the livelihood of affected communities. To explore this hypothesis we developed the first scoping review to identify and characterize the global literature on snakebite in domestic animals. Three bibliographic databases (PubMed, Web of Science and Agricola) were searched using terms related to snake, snakebite and domestic animals for publications up to December 31st, 2016. Two independent reviewers screened publications applying inclusion/exclusion criteria to select relevant material. Relevant information was then extracted from the selected literature. The global literature on snakebite in domestic animals (n = 143 observational studies, reviews and letters) mainly represented North America, Europe and Australia (69%) with less information from Central and South America, Asia and Africa (31%). Observational studies (n = 119) mostly concerned pets (78%) and to a lesser extent livestock (22%). Thirty-four snake species were reported as responsible for bites in domestic animals. WHO’s Medically Important Venomous Snakes were more frequently involved. The social-ecological determinants of snakebite were poorly documented but the reviewed literature suggested a strong seasonality and a diversity of habitat. Snakebite in animals caused neurotoxic, cytotoxic and hemotoxic envenomation syndromes similar to humans and death. Half of publications on envenomed livestock reported a fatality rate above 47%. There was no literature on the indirect impact of snakebite on livelihood caused by animal morbidity and mortality. The results of this scoping review suggest a high and under-reported burden in terms of mortality in animals and a potential economic impact of snakebite in terms of losses in livelihood of affected communities. However, major knowledge gaps with respect to impact of snakebite on livestock and livelihood were identified. Filling these gaps is necessary for a full understanding of the impact of snakebite and to raise scientific, political and public awareness on this neglected issue.